A law and finance analysis of initial public offerings - Holmén, Martin; Högfeldt, Peter (Journal of Financial Intermediation, 2004)
Do families keep control of their firms because they, operating in an environment with weak protection of minority shareholders, fear being exploited by management after the IPO? Or is ownership concentration due to the value families attach to control? We find a positive relation between use of security designs that separate votes from capital and frequency of family-controlled firms in Sweden and other countries. It is not caused by differences in legal regimes or in minority protection. Since control blocks are never sold piecemeal to preserve control value, ownership remains highly concentrated. Family-controlled firms trade at a discount because of the misallocation of control rights to heirs who make inefficient decisions, not because of extraction of pecuniary benefits.